Tarbawi Interpretation in Indonesia - Irfan Nurzaman; Fuad Salim; Zikro Elok Al Faein; Edi Komarudin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study examines the significant role of Tafsir Tarbawi in the development of Islamic education in Indonesia. Tafsir Tarbawi not only serves as a source of values but also as an epistemological and theological foundation for building Islamic education concepts and theories. Despite the significant role of Tafsir Tarbawi, there are still fundamental questions regarding its nature, validity, and acceptance within the academic community. The objectives of this study are to understand the definition and relevant verses of Tafsir Tarbawi, identify key Tafsir Tarbawi scholars in Indonesia, and comprehend the characteristics and approaches of Tafsir Tarbawi. The research method used is a qualitative study with a descriptive-analytical approach through literature review, referring to books, articles, and journal entries related to Tafsir Tarbawi. The results of the study indicate that Tafsir Tarbawi is a systematic study of Qur'anic exegesis that investigates the concepts of Islamic education, including definitions, objectives, methods, media, evaluation, and management. Key Tafsir Tarbawi scholars in Indonesia include Prof. Dr. H. Abuddin Nata, MA., among others. The characteristics of Tafsir Tarbawi are evident in the exegesis approach that views tafsir from an educational perspective. This study is expected to enhance understanding of the role of Tafsir Tarbawi in Islamic education and address the challenges and opportunities that may arise in the future.